Effectiveness of ultrasound-guided percutaneous electrolysis intratendon (epi) in the treatment of insertional patellar tendinopathy in soccer players - Sánchez-Ibáñez, J. M.; Alves, R.; Polidori, F.; Valera, F.; Minaya, F.; Valles-Marti, S.; Baños, L. (British Journal of Sports Medicine, 2013)
Introduction Patellar tendinopathy or `jumper's knee` is considered more of a degenerative (tendinosis) than a non-inflammatory process (tendinitis). Recent histopathological studies have shown the absence of inflammatory cells in this type of pathology and demonstrated the presence of myxoid degeneration, disruption of the collagen fibres and signs of hypoxia in tenocytes and resident macrophages. Percutaneous electrolysis intratendon (EPI) is a non-thermal electrochemical ablation through a cathodic flow in the region or clinical focus of the degenerated tendon. EPI produces the dissociation of water, salts and amino acids of the extracellular matrix creating new molecules through ionic instability. The aim of this research is to prove the effectiveness of EPI in the treatment of patellar tendinopathy and to observe the healing time in 23 football players. Methods A prospective study was performed between January and December 2011 involving 23 patients, all soccer players diagnosed with patellar tendinopathy and referred to the Physiotherapy Service of the Sports Recovery Center, CEREDE, in Barcelona. All patients were football players (n=23), 23 men (100%) and no woman (0%). In the total study population (n=23) the clinical location corresponded to the osteotendinous junction of the lower pole of the patella, leading to the diagnosis of enthesopathy of the proximal patella. Based on the first observation and according to their score on the questionnaire, Victorian Institute of Sport Assessment-Patellar Tendon (VISA-P), we classified the patients into two groups: Group-1 (worse prognosis, n=12) who scored a VISA-P=50 (52.2%) and Group-2 (better prognosis, n=11) with VISA-P score>50 (47.8%). All patients underwent EPI technique that was applied with an intensity of 3 mA during a period of 4 s, using the approved electro stimulator EPI (Epimedical scp, Barcelona 08017, Spain). The intervention was performed under ultrasound guidance with a portable ultrasound (General Electric LogicE).Results Regarding the VISA-P score, Group 1 (n=12) in the first examination had a mean VISA-P score of 33.67 (SD±12.27, 95% CI 25.87 to 41.6) and in the last observation an average of 83.17 (SD±15.36, 95% CI 73.41 to 92.93), showing a statistically significant improvement in the results of the VISA-P questionnaire (p=0.005). Group 2 (n=11) in the first observation had a mean VISA-P of 68.09 (SD±10.50, 95% CI 61.04 to 75.15) and in the last one, an average of 85.27 (SD±6.15, 95% CI 81.14 to 89.40) with statistically significant differences between the scores of the first and last observation (p=0.005). In Group 1 (n=12), the average healing time was 4.66 weeks (95% CI 3.25 to 6.08) while in the group with the better prognosis (Group 2, n=11) it was 2.18 weeks (95% CI 2.57 to 4.39), both with statistically significant differences (p=0.001). Regarding the estimation of the number of interventions with EPI needed to achieve healing, in the group with the worse prognosis (Group 1, n=12) the average number was 5.0 EPI sessions (95% 3.59 to 6.40) while in the group with better prognosis (Group 2 n=11), the mean number of sessions needed to achieve healing was 2.45 EPI sessions. Conclusions The ultrasound guided percutaneous electrolysis technique (EPI) has proved to be highly effective in the treatment of proximal patellar enthesopathy in a population of soccer players, with a significant improvement in 91.7% of the total sample (n=22), as measured by the Victorian Institute of Sport Assessment-Patellar Tendon (VISA-P) questionnaire. An analysis of Kaplan-Meier survival allowed us to estimate the time and number of sessions of EPI technique needed to achieve cure for both the group with worse prognosis (Group 1) and for the group with better prognosis (Group 2), independent of the stadium of the patient according to Blazina's Classification. EPI technology has proven to be very effective and therefore should not be a criterion for surgical intervention patients that, at first observation, are in stage III of Blazina's Classification. EPI technology has also proven to be effective in curing insertional patellar tendinopathy in soccer players regardless of duration and evolution of the clinical symptoms.